RESPONSE OF VEGETATIVE GROWTH OF TOMATO (Solanum lycopersicum L. VAR. MIRA) DUE TO PGPR (PLANT GROWTH-PROMOTING RHIZOBACTERIA) COMBINED WITH COMPOST AND NPK FERTILIZER - Parluhutan SIAHAAN; Nevada Indah MANGINDAAN; Marina Flora Oktavine SINGKOH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study aims to determine the growth response of tomato (Solanum lycopersicum L.) plants after the application of PGPR combined with compost and NPK fertilizer on vegetation. The tested parameters include the plant height, number of leaves, wet and dry weight, and root volume of plants. The method used was a non-factorial trial with five treatments and replications, whereby P0 was a control, P1 was given PGPR, P2 composted fertilizer and PGPR, P3 NPK and PGPR, and P4 was given only NPK. Analysis of Variance (ANOVA) was performed on the data and continued with the Least Significance Different Test (LSD). The results showed no significant difference in the plant height, number of leaves, wet and dry weight of PGPR treatment plants with a combination of compost fertilizer and NPK; hence PGPR was used to compensate for NPK. Although the root volume parameters showed significant differences, which was evident in the application of NPK in combination treatment of PGPR, compost fertilizer, or NPK..